Omplacering av hundar - Lilja, Sara (2012)
Many dogs in Sweden are put up for adoption at the Swedish buy- and sales site”Blocket”. This because in Sweden, rescue shelters mostly takes in dogs that have been confiscated by the police. The aim of this study was to investigate what kind of dogs that are put up for adoption and why owners put their dog up for adoption and also compare the results with those from other countries. 800 dog advertisements from “Blocket” were collected in the study between January 31st and April 10th 2012. Breed, residency, reason, pure or mix breed, sex, racial group and if the dog were castrated or not was recorded. The results showed that pure breed dogs were more common to be put up for adoption. The proportion of the sexes was even but male dogs were slightly more common than female dogs. Dogs from the countryside and apartments were more often put up for adoption than dogs from villas. 89 % of the 800 dogs were not castrated and 76 % of the uncastrated dogs were male dogs. The most common breed group that was put up for adoption was the pet dogs followed by the mix breed dogs with breeds from different breed groups. The third most common breed group was the terriers. German Shepherd followed by the American Staffordshire, Chihuahua and Rottweiler were the most common breeds among the pure- and mix breed dogs. The main reason to put up the dog for adoption was for personal reasons followed by lack of time, relationship changes and behaviour problems. When it came to each reason behind the adoption, the proportion of the male and the female dogs was even. Many owners did not give complete information about the dog’s behaviour problem or the reason behind the adoption. The results of this study show that there are many factors involved in why dogs in Sweden has been put up for adoption. It is also many different kind of breeds that are being put up for adoption in Sweden. It is important that new owners get correct and complete information about the dog, especially if the dog has behaviour problems in order to be better prepared of what to expect.